2009
DOI: 10.1103/physrevb.79.075101
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum critical paraelectrics and the Casimir effect in time

Abstract: We study the quantum paraelectric-ferroelectric transition near a quantum critical point, emphasizing the role of temperature as a "finite size effect" in time. The influence of temperature near quantum criticality may thus be likened to a temporal Casimir effect. The resulting finitesize scaling approach yields 1 T 2 behavior of the paraelectric susceptibility (χ) and the scaling form, recovering results previously found by more technical methods. We use a Gaussian theory to illustrate how these temperature-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 58 publications
(114 reference statements)
6
40
0
Order By: Relevance
“…At higher temperatures the T 2 contribution from the mean-field term dominates, which is also characteristic of quantum critical behavior and is in good agreement with recent experimental results [3]. We note that the T 2 behavior is recovered by other models, including a diagrammatic resummation [5,6], the quantum spherical model [22], renormalization group studies [23,24], a self-consistent phonon model [3], and an analogy to the temporal Casimir effect [9]. The behavior has also been observed experimentally [3,16,17].…”
Section: B Inverse Susceptibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…At higher temperatures the T 2 contribution from the mean-field term dominates, which is also characteristic of quantum critical behavior and is in good agreement with recent experimental results [3]. We note that the T 2 behavior is recovered by other models, including a diagrammatic resummation [5,6], the quantum spherical model [22], renormalization group studies [23,24], a self-consistent phonon model [3], and an analogy to the temporal Casimir effect [9]. The behavior has also been observed experimentally [3,16,17].…”
Section: B Inverse Susceptibilitysupporting
confidence: 88%
“…One suggestion is that new phenomena are driven by the coupling of acoustic to optical phonons [3,6,9]. However, inspired by the ramifications of quantum fluctuations in ferromagnets [10], we show that the transverse coupling of fluctuating phonons can drive a first order metaelectric transition.…”
Section: Introductionmentioning
confidence: 80%
“…We focus here on the ferroelectric (FE) QCP which is a key part of the discussion of FE behaviour, particularly in displacive quantum paraelectrics [6,7]. The behaviours that may occur near or as a result of such an FE QCP have been explored in various contexts [6][7][8][9][10][11][12][13], and the list of systems where the effects of quantum fluctuations can be observed is expanding, with temperatures up to ∼ 60K in some organic charge-transfer complexes [10,14].The concept of dynamical multiferroicity was introduced recently as the dynamical counterpart of the Dzyaloshinskii-Moriya mechanism, reflecting the symmetry between electric and magnetic properties [15]. In the Dzyaloshinskii-Moriya mechanism [16-18], ferroelectric polarisation is caused by a spatially varying magnetic structure, leading to strong coupling between ferroelectricity and magnetism [19][20][21].…”
mentioning
confidence: 99%
“…We focus here on the ferroelectric (FE) QCP which is a key part of the discussion of FE behaviour, particularly in displacive quantum paraelectrics [6,7]. The behaviours that may occur near or as a result of such an FE QCP have been explored in various contexts [6][7][8][9][10][11][12][13], and the list of systems where the effects of quantum fluctuations can be observed is expanding, with temperatures up to ∼ 60K in some organic charge-transfer complexes [10,14].…”
mentioning
confidence: 99%
“…18 It has recently been suggested that unexpected behavior in the quantum phase transition of SrTiO 3 involves strain effects. 19,20 Understanding the role of the strain dynamics in ferroelectric domain walls may help explain some of these results.…”
Section: Introductionmentioning
confidence: 99%